INTEGRATING MULTIMODAL TEXTS IN GENRE-BASED APPROACH: TEACHER’S AND STUDENTS’ CHALLENGES AND BENEFITS - Hidayat, R. Rizkiki Azkia; Fajriah, Yustika Nur; Nugraha, Irsyad (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
Integrating multimodal text in Genre-Based Approach (GBA) is demanded in our recent era as well as the curriculum. Teachers and students will definitely experience challenges and benefits in the teaching and learning process. Thus, this study aimed to find out the challenges and benefits of integrating multimodal text in GBA. A qualitative study was employed as the methodology. This research was conducted at a public senior high school in West Java, involving one English teacher and 36 students from the twelfth grade as a research participant. The data was collected by classroom observation and interviews. The results were analyzed using inductive analysis by dividing the findings into two main themes, the challenges and the benefits experienced by the teacher and students. The research shows that major challenges that students and the teacher faced, included difficulties with resource accessibility, technical proficiency, time allocation, and preparation stage. As for the benefits, the results point to enhanced communication creativity, improved critical thinking abilities, accommodated differences in student learning styles, and increased engagement among students as essential advantages. In conclusion, integrating multimodal text in GBA provides more benefits than challenges for both the teacher and students. Therefore, it is recommended to integrate multimodal text in GBA, especially in teaching English